2020
DOI: 10.1021/acs.jproteome.0c00229
|View full text |Cite
|
Sign up to set email alerts
|

Improved Integrated Whole Proteomic and Phosphoproteomic Profiles of Severe Acute Pancreatitis

Abstract: Severe acute pancreatitis (SAP) is caused by complicated biological factors, and revealing its complex pathogenesis by single-target analysis is difficult. Systematic studies have developed slowly because extraction of degradable pancreatic proteins exposed to multiple proteases is challenging. We present integrated whole proteomic and phosphoproteomic profiles of SAP rats based on a modified protein extraction strategy with less protein degradation. Data-dependent acquisition (DDA) and data-independent acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Ga 3+ -based immobilized metal affinity chromatography (Ga-IMAC) was used to enrich phosphopeptides in this study since it was shown to be reproducible and specific in purifying phosphoproteins in Arabidopsis seedlings [ 26 ] and efficient in enriching phosphopeptides in Arabidopsis inflorescence tissues [ 27 ] and in rat pancreas [ 28 ]. A spectral library for phosphoproteome was constructed using Ga-IMAC enrichment followed by high-pH reversed-phase fractionation, LC-MS/MS analysis and identification by Proteome Discoverer ( Figure 1 and Table S1 , FDR < 1% for PSMs and peptide groups).…”
Section: Resultsmentioning
confidence: 99%
“…Ga 3+ -based immobilized metal affinity chromatography (Ga-IMAC) was used to enrich phosphopeptides in this study since it was shown to be reproducible and specific in purifying phosphoproteins in Arabidopsis seedlings [ 26 ] and efficient in enriching phosphopeptides in Arabidopsis inflorescence tissues [ 27 ] and in rat pancreas [ 28 ]. A spectral library for phosphoproteome was constructed using Ga-IMAC enrichment followed by high-pH reversed-phase fractionation, LC-MS/MS analysis and identification by Proteome Discoverer ( Figure 1 and Table S1 , FDR < 1% for PSMs and peptide groups).…”
Section: Resultsmentioning
confidence: 99%
“…Housekeeping genes for basic cell maintenance are also suggested to maintain constant expression levels in all cells, under all conditions [ 14 ]. Our analysis revealed that housekeeping proteins, including ACTB, PGK1, RPS18, RPS27A, RPL11, RPL19, RPL32, NONO, ARHGDIA, TUBA1B, TUBA1C, TUBB4B, and HSP90B1 were stably expressed in both the control and MA groups ( Supplementary Figure 2C ), demonstrating the reliability of the proteomic sequencing results [ 15 ].…”
Section: Resultsmentioning
confidence: 76%
“…Additionally, it was surprisingly that the majority of altered proteins revealed by KEGG that are involved in energy metabolism and amino acid metabolism showed a pattern of pullback after growing at the inflammatory peak, which was different from the prior proteomics findings. ,, For example, prior proteomics studies on the CER-induced AP rat model found that important enzymes involved in the TCA cycle, glycolysis, or BCAA metabolism were reduced . Based on a rat model of SAP, decreased oxidative phosphorylation, carbon metabolism, and degradation of valine, leucine, and isoleucine were also observed . This heterogeneity needed to be further demonstrated and compared.…”
Section: Discussionmentioning
confidence: 99%
“…Severity indices of CER-induced AP in mice; upset plot showing overlapping proteins in 30 GO terms; relationships between AP dysregulated proteins and KEGG pathways (top 10); relative expressions of SPIs, filaments, and HSP 70s; enrichment analysis of 306 proteins that were screened by time-course analysis after the removal of greater abundances proteins; mass list of DIA windows; and list of 25…”
Section: ■ Associated Contentmentioning
confidence: 99%
See 1 more Smart Citation